Ecological Wisdom of The Bajo Tribe in The Perspective of Fiqh al-Bi’ah and Green Constitution - Chanifah, Nur; Luth, Thohir; Rohmah, Siti; Kholish, Moh. Anas; Zaini Muchlis (AL-IHKAM: Jurnal Hukum & Pranata Sosial, 2024)
The Bajo community, as a traditional maritime group, has long practiced marine environmental conservation, such as avoiding marine pollution and protecting endangered species. However, these conservation efforts are often perceived as lacking a firm legal foundation within both formal legal systems and Islamic law, making local wisdom-based conservation initiatives susceptible to neglect by both the government and the broader society. This study aims to analyze the marine environmental conservation practices of the Bajo community from the perspectives of Islamic environmental jurisprudence and the concept of green constitutionalism. The study conducted a qualitative approach. Data were collected through interviews and Focus Group Discussions (FGDs) with Bajo community members, religious leaders, and relevant stakeholders. The findings reveal that the unwritten customary regulations of the Bajo community emphasize the sanctity of the sea and promote a subject-to-subject relationship between humans and nature. The conservation practices of the Bajo community align with the principles of Islamic environmental law (fiqh al-bi’ah), particularly the principle of prioritizing environmental sustainability for the welfare of humanity. Furthermore, the study finds that Bajo conservation traditions have adopted the principles of green constitutionalism enshrined in Article 28 H of the 1945 Constitution of Indonesia, which ensures the right to a healthy and sustainable environment.